Stem and progenitor cells from peripheral blood - Soker, Shay (Henry Stewart Talks, 2014)
Adult stem and progenitor cells have been found circulating in peripheral blood, allowing them to reach and integrate into all tissues, Bone marrow is most likely the source of these cells, including endothelial progenitor cells (EPCs), Identification of circulating EPCs point to the possibility that vasculogenesis-mediated neovascularization, previously believed to be restricted to the embryonic stages, continues into adulthood